2007
DOI: 10.1080/00048670601057718
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Profile of Major Depressive Disorder in Women with Eating Disorders

Abstract: Clinicians treating individuals with new-onset ED or MDD should remain vigilant for the emergence of additional psychopathology, especially during the initial 3 year window following the onset of the first disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 51 publications
4
50
0
4
Order By: Relevance
“…12 Present findings seem to be in agreement with previous results showing that UMs are more frequent among suicide cases, 13 persistent mood-disordered patients 14 and among women with symptoms of depression, 15 which usually overlap with ED. [16][17][18] In addition, we have previously reported that PMs are less frequent among schizophrenic patients than among healthy subjects (2.3 vs 8.5%, respectively), 19 which would be in accordance with lower scores on a measure of risk to psychopathology or general distress also found among PM healthy volunteers. 11 Moreover, PMs seem to perform better on a cognitive task that assesses sustained attention, a trait characteristically impaired in patients with schizophrenia, bipolar depression and attention and deficit hyperactive disorder.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…12 Present findings seem to be in agreement with previous results showing that UMs are more frequent among suicide cases, 13 persistent mood-disordered patients 14 and among women with symptoms of depression, 15 which usually overlap with ED. [16][17][18] In addition, we have previously reported that PMs are less frequent among schizophrenic patients than among healthy subjects (2.3 vs 8.5%, respectively), 19 which would be in accordance with lower scores on a measure of risk to psychopathology or general distress also found among PM healthy volunteers. 11 Moreover, PMs seem to perform better on a cognitive task that assesses sustained attention, a trait characteristically impaired in patients with schizophrenia, bipolar depression and attention and deficit hyperactive disorder.…”
Section: Discussionsupporting
confidence: 75%
“…15 In addition, altered serotonin neurotransmission and associated comorbid affective disorders are frequently described in ED. [16][17][18] Thus, in light of these observations, we aimed to analyze the relationship between CYP2D6 genetic polymorphism and susceptibility to ED.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported increased BDNF levels for ED [11] . Moreover, high comorbidity between ED and Axis I or Axis II disorders, such as affective disorders, personality disorders, anxiety disorders, obsessive compulsive disorders, impulse control disorders and substance abuse, has been described [13][14][15][16][17][22][23][24] . Accordingly, the degree of comorbidity could be modulated by BDNF expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported in the literature [22][23][24] and are linked to ED severity [25] and poorer prognosis [26] .…”
mentioning
confidence: 99%
“…7 AN is often comorbid with major depressive disorder, anxiety disorders, and multiple somatic complications. [8][9][10][11][12] Although most individuals recover, ~25% develop a chronic and relapsing course. 13 AN ranks among the ten leading causes of disability among young women 14 and has one of the highest mortality rates of any psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%